PENGARUH STRES KERJA TERHADAP KINERJA PERAWAT MELALUI KEPUASAN KERJA (Studi pada Perawat Instalasi Rawat Inap Rumah Sakit Militer Kota Malang) - Faudin, Mokhamad Afif; Samiadji, Samiadji (Magister Manajemen Universitas Wisnuwardhana, 2020)
The purpose of this research is to determine the direct effect of work stress on performance, job stress on job satisfaction, job satisfaction on performance, and the indirect effect of job stress on performance through nurse job satisfaction. The research design used is explanatory research. The number of nurses in the Inpatient Installation of the Military Hospital of Malang City was 154 people, while the respondents in this study were 106 people. The data collection method in this study used a questionnaire measured by the linkert scale. While the data analysis used descriptive data analysis techniques and Path Analysis. The results of this study are: (1) Job Stress has a significant effect on Nurse Performance, (2) Job Stress has a significant effect on Nurse Job Satisfaction, (3) Job Satisfaction has no significant effect on Nurse Performance, (4) There is no indirect effect of Job Stress on Nurse Performance through Job Satisfaction. This shows that nurses who serve in the Inpatient Installation of Military Hospitals in Malang City are able to control work stress on nurses, so that the job satisfaction felt by nurses has no effect on nurse performance. Keywords: job stress, performance, job satisfaction